8th EASN-CEAS Workshop on Manufacturing for Growth and Innovation - Pantelakis, Spiros (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue contains selected papers from works presented at the 8th EASN-CEAS (European Aeronautics Science Network-Council of European Aerospace Societies) Workshop on Manufacturing for Growth and Innovation, which was held in Glasgow, UK, 4-7 September 2018. About 150 participants contributed to a high-level scientific gathering providing some of the latest research results on the topic, as well as some of the latest relevant technological advancements. ?ine interesting articles, which cover a wide range of topics including characterization, analysis and design, as well as numerical simulation, are contained in this Special Issue.